Advantages and disadvantages of telemedicine during the COVID-19 pandemic era among physicians in Taif, Saudi Arabia - Mubaraki, Adnan A. (Saudi Med J, 2021)
OBJECTIVES: To evaluate the advantages and disadvantages of telemedicine among physicians during the COVID-19 pandemic. To assess the awareness about telemedicine among physicians and determine their opinions about telemedicine in the post-pandemic era. METHODS: A cross-sectional study was conducted at government hospitals (King Faisal Medical Complex [KFMC]-King Abdulaziz Specialist Hospital [KASH]) in Taif, Kingdom of Saudi Arabia (KSA), from May-August 2020. Taif is a small city in the western region of KSA with a population of 689,000 and 2 main hospitals (KFMC & KASH) which also serve rural areas close to Taif city. A total of 36 physicians practiced telemedicine, only 25 physicians accepted to participate in this study. RESULTS: Thirty-six percent of the responders believed that telemedicine could improve the effectiveness of therapeutic intervention and 44% believed that the quality of care was enhanced using telemedicine. Difficulty in reaching the correct diagnosis due to the lack of physical examination was one of the disadvantages that faced the participants. CONCLUSION: Telemedicine should be part of medical services but should not completely replace physicians’ personal interaction. Telemedicine could be continued for stable remotely residing patients even after the COVID-19 pandemic.